VALIDITY OF DEVELOPMENT OF THE GAME WHO WANTS TO BE A MILLIONAIRE COLLOID IN MAN 3 BANJARMASIN (NUKLEO SAINS : JURNAL PENDIDIKAN IPA, 2023)
This study aims to determine the validity of the development of educational game who wants to be a millionaire on colloidal material for class XI students of MAN 3 Banjarmasin with the data source used consists of 1 material expert who is a chemistry teacher and 1 media expert. Data sources used consisted of 1 material expert who is a chemistry teacher and 1 media expert who is a lecturer. who is a lecturer. The type of research used is Research and Development (R&D) model (Define, Design, Develop, and Disseminate). The research results showed that the material expert validation value was 74% and the media expert validation value was 79% so that the game developed could be categorized as valid.